2008
DOI: 10.1159/000143110
|View full text |Cite
|
Sign up to set email alerts
|

Homing of Mesenchymal Stem Cells

Abstract: Mesenchymal stem cells (MSCs) are primarily fibroblast-like cells. Yet, once studied under conditions of shear stress when flowing along endothelial cells in vitro or in blood vessels, as well as in classic migration assays such as chemotaxis assays, MSCs have recently been found to function similarly to leukocytes in many ways. Firstly, MSCs express several homing receptors which are typically activated during extravasation of leukocytes. Secondly, some of these receptors are definitely functional, and requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 49 publications
1
28
0
Order By: Relevance
“…The identification of the adhesion molecules and surface receptors that guide the vascular adhesion of MSCs has been aided by comparisons to the similar activities of HSCs and leukocytes (reviewed in ref. 115). Like hematopoietic cells, MSCs appear to utilize E-selectin for vascular adhesion, but lack other hematopoietic cell adhesion molecules such as L-selectin, β2 integrins and platelet endothelial cell adhesion molecule-1 (PECAM-1)/CD34 that facilitate the rolling of HSCs on vasculature and their subsequent transmigration through the endothelial wall.…”
Section: Msc Homing To Tumorsmentioning
confidence: 99%
“…The identification of the adhesion molecules and surface receptors that guide the vascular adhesion of MSCs has been aided by comparisons to the similar activities of HSCs and leukocytes (reviewed in ref. 115). Like hematopoietic cells, MSCs appear to utilize E-selectin for vascular adhesion, but lack other hematopoietic cell adhesion molecules such as L-selectin, β2 integrins and platelet endothelial cell adhesion molecule-1 (PECAM-1)/CD34 that facilitate the rolling of HSCs on vasculature and their subsequent transmigration through the endothelial wall.…”
Section: Msc Homing To Tumorsmentioning
confidence: 99%
“…They found that CD44 in stem cells enables them to bind to E-selectin [43]. Other molecules and chemokines that are involved in migration of stem cells to sites of damaged tissue are VCAM-1, ICAM-1, ICAM-2, transforming growth factor-β (TGF-β) and MCP-1 [27,44]. The amount of host-derived stem cells contributing to graft neointima has not been assessed accurately.…”
Section: Smooth Muscle Cells and Smooth Muscle-like Cellsmentioning
confidence: 99%
“…The process of PBSC recruitment in a tissue takes place predominantly at the level the postcapillary venule, in a manner similar to neutrophils (Henschler et al, 2008).…”
Section: Extravasation and Recruitmentmentioning
confidence: 99%